2019
DOI: 10.21470/1678-9741-2019-0131
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Carotid Duplex Scanning in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: ObjectiveThe aim of this study was to determine the prevalence and risk factors of carotid artery stenosis (CAS) using carotid duplex ultrasound in patients undergoing coronary artery bypass grafting (CABG).MethodsThis retrospective study was conducted between January 2017 and January 2018 and included 166 consecutive patients [130 males (78.31%), 36 females (21.69%); mean age: 64.25±9.78 years] who underwent elective and isolated CABG. Patients who had significant CAS (≥50% stenosis) were compared with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A study by Kara on the risk of carotid artery stenosis in patients undergoing CABG found that of the eight patients with mean age 48 years diagnosed with ≥70% stenosis, 50% were < 70 years old. If the study had chosen to perform selective carotid DUS only in patients aged ≥70 years, four patients would not have been detected [25]. In our study, 16 patients in the low-risk group were diagnosed with ≥70% stenosis.…”
Section: Discussionmentioning
confidence: 79%
“…A study by Kara on the risk of carotid artery stenosis in patients undergoing CABG found that of the eight patients with mean age 48 years diagnosed with ≥70% stenosis, 50% were < 70 years old. If the study had chosen to perform selective carotid DUS only in patients aged ≥70 years, four patients would not have been detected [25]. In our study, 16 patients in the low-risk group were diagnosed with ≥70% stenosis.…”
Section: Discussionmentioning
confidence: 79%
“…Atherosclerosis is a systematic inflammatory disease and, therefore, a strong relation between coronary atherosclerosis and carotid artery stenosis (CAS) has commonly been assumed [ 6 - 7 ]. Moreover, there is evidence to suggest that significant CAS is common among patients undergoing cardiac surgery with a high risk of critical neurological events [ 8 - 9 ]. Approximately 30% of annual global mortality is attributable to cardiovascular disease, while an additional 10% is attributable to cerebrovascular events [ 10 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the systemic nature of atherosclerosis, patients with severe CAD requiring CABG frequently exhibit severe carotid artery stenosis as well. 1,2 One of the most devastating complications following CABG is stroke and its frequency is estimated to 1-5%. [3][4][5][6] Cerebral hypoperfusion due to severe carotid disease is one of the risk factors for stroke during or shortly after CABG.…”
Section: Introductionmentioning
confidence: 99%